Prepare citizens in a global era: can intercultural education help? - Santos Rego, Miguel Ángel (Avances en Supervisión Educativa, 2009)
In this article we try to look around the globalization phenomenon on which -and with the only exception of the liturgical repetition of anti-liberal principles- people from certain academic circles seem to have settled ourselves. No doubt a different world is possible, but it ought to be a more practical and less rhetorical one, especially when we tackle the problem of a change in international order for which firm decisions are required in order to face poverty, conflicts resolution, respect for human rights and environmental care. What we claim for it is simply sustainable development, which we deprive of exclusively ecological connotations to categorize it under the postulates of multicultural education: recognition, fairness, cooperation and civic apprenticeship. Therefore, let us make it possible that multicultural education can be regarded as the other side of globalization.